El-Fógǎha, Oasi Berberofona Del Fezzân - Paradisi, Umberto (Rivista degli studi orientali, 1961)
Keywords: Linguistique -- Djebel Nefousa

Ibaditica I. Tasmiya shuyūkh Nafūsa - Lewicki, Tadeusz (Rocznik Orientalistyczny, 1961)
Based on Anonymous: Dhikr Asmā’ baʿḍ Shuyūkh al-Wahbiyya, in appendix to Shammākhī: Siyar (pp. 588-598), complemented with other sources, notably Darjīnī: Ṭabaqāt al-Mashāyikh, Shammākhī: Siyar, Masqueray 1878a, and other Siyar books. First Lewicki treats a short list of authors mentioned at the end of Dhikr Asmā’ baʿḍ Shuyūkh al-Wahbiyya (pp. 89-94), then he edits and comments on the text of Tasmiyat Shuyūkh Nafūsa, which constitutes the first part of Dhikr Asmā’ and which contains a list of more than 90 personalities of the tribe Nafūsa (pp. 94-120).
Keywords: Linguistique -- Djebel Nefousa